Urban commons in debate: from the commons in the city to the city as a common? - Tonucci Filho, João Bosco Moura (2019)
In different cities around the world, the idea of urban commons has been invoked bymovements, researchers and even public policymakers to claim and protect against privatization a set of urbanresources and goods that could be more widely shared between its inhabitants. The purpose of this article isto discuss the most recent literature dealing with the urban commons, encompassing studies ranging fromcommon resources in the city to those who treat the city itself (and urban life) as a common. Initially, the recentemergence of this literature is contextualized, and its main theoretical debates and theoretical perspectives aretraced. Next, it is discussed how the resources and common spaces in the city have been treated and studied bydifferent theoretical approaches. Finally, we debate how the idea of the city itself as a common has received theattention of different theorists so far, pointing out the advances and limitations of these approaches to thinkthe city beyond the public and the private.